Genomic analyses reveal evolutionary and geologic context for the plateau fungus Ophiocordyceps sinensis - Jie Liu (Chinese Medicine, 2020)
Abstract Background Ophiocordyceps sinensis, which is only naturally found in the high-elevation extreme environment of the Tibetan Plateau, has been used in traditional Chinese medicine. Information concerning the evolutionary and geologic context of O. sinensis remains limited, however. Methods We constructed the high-quality genome of O. sinensis and provided insight into the evolution and ecology of O. sinensis using comparative genomics. Results We mapped the whole genome of the anamorph/asexual form Hirsutella of O. sinensis using Illumina and PacBio sequencing technologies and obtained a well assembled genome of 119.2 Mbp size. Long-read Single Molecule Real Time (SMRT) sequencing technology generated an assembly with more accurate representation of repeat sequence abundances and placement. Evolutionary analyses indicated that O. sinensis diverged from other fungi 65.9 Mya in the Upper Cretaceous, during the uplift of the Tibetan Plateau. Gene family expansions and contractions in addition to genome inflation via long terminal repeat (LTR) retrotransposon insertions were implicated as an important driver of O. sinensis divergence. The insertion rate of LTR sequences into the O. sinensis genome peaked ~ 30–40 Mya, when the Tibetan Plateau rose rapidly. Gene Ontology (GO) enrichment analysis suggested that O. sinensis contained more genes related to ice binding compared to other closely related fungi, which may aid in their adaptability to the cold Tibetan Plateau. Further, heavy metal resistance genes were in low abundance in the O. sinensis genome, which may help to explain previous observations that O. sinensis tissues contain high levels of heavy metals. Conclusions Our results reveal the evolutionary, geological, and ecological context for the evolution of the O. sinensis genome and the factors that have contributed to the environmental adaptability of this valuable fungus. These findings suggest that genome inflation via LTR retrotransposon insertions in O. sinensis coincided with the uplift of the Tibetan Plateau. LTRs and the specific genetic mechanisms of O. sinensis contributed to its adaptation to the environment on the plateau.